TEMBILAHAN COMMUNITY’S OF THETERM E-WALLET IN THE USE OF DIGITAL PAYMENT APPLICATIONS - Diana; M. Raihan; Asniati Bindas (Indragiri Research Center (ingreat), 2025)
The development of digital technology has driven changes in the community's payment system through the use of digital payment applications or e-wallets. In Tembilahan, the community has utilized various digital payment applications in their daily transactions. However, the community's understanding of the term e-wallet as a digital payment concept is formed through their experience of using the application and the surrounding social context. This study aims to understand the Tembilahan community's understanding of the term e-wallet in the use of digital payment applications. This study uses a qualitative method with a descriptive approach. Data collection was conducted through in-depth interviews, observations, and documentation of the Tembilahan community who use digital payment applications. Data analysis was carried out using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results of the study show that the public understands e-wallets based on the functions and experience of using digital payment applications, rather than based on a formal understanding of the term. This understanding is influenced by usage habits, social interactions, access to information, and digital financial literacy. This study is expected to provide a contextual overview of the public's understanding of e-wallets and serve as a consideration in the development of digital financial literacy programs that are more suited to the characteristics of the community.